An indentation-based framework for probing the glycosaminoglycan-mediated interactions of collagen fibrils. (April 2023) - Ostadi Moghaddam, A.; Arshee, M.R.; Lin, Z.; Sivaguru, M.; Phillips, H.; McFarlin, B.L.; Toussaint, K.C.; Wagoner Johnson, A.J.
Abstract: Microscale deformation processes, such as reorientation, buckling, and sliding of collagen fibrils, determine the mechanical behavior and function of collagenous tissue. While changes in the structure and composition of tendon have been extensively studied, the deformation mechanisms that modulate the interaction of extracellular matrix (ECM) constituents are not well understood, partly due to the lack of appropriate techniques to probe the behavior. In particular, the role of glycosaminoglycans (GAGs) in modulating collagen fibril interactions has remained controversial. Some studies suggest that GAGs act as crosslinkers between the collagen fibrils, while others have not found such evidence and postulate that GAGs have other functions. Here, we introduce a new framework, relying on orientation-dependent indentation behavior of tissue and computational modeling, to evaluate the shear-mediated function of GAGs in modulating the collagen fibril interactions at a length scale more relevant to fibrils compared to bulk tests. Specifically, we use chondroitinase ABC to enzymatically deplete the GAGs in tendon; measure the orientation-dependent indentation response in transverse and longitudinal orientations; and infer the microscale deformation mechanisms and function of GAGs from a microstructural computational model and a modified shear-lag model. We validate the modeling approach experimentally and show that GAGs facilitate collagen fibril sliding with minimal crosslinking function. We suggest that the molecular reconfiguration of GAGs is a potential mechanism for their microscale, strain-dependent viscoelastic behavior. This study reveals the mechanisms that control the orientation-dependent indentation response by affecting the shear deformation and provides new insights into the mechanical function of GAGs and collagen crosslinkers in collagenous tissue. Graphical abstract: Image 1